2021
DOI: 10.3390/biom11091282
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of the DUF34 Protein Family Suggests Role as a Metal Ion Chaperone or Insertase

Abstract: Members of the DUF34 (domain of unknown function 34) family, also known as the NIF3 protein superfamily, are ubiquitous across superkingdoms. Proteins of this family have been widely annotated as “GTP cyclohydrolase I type 2” through electronic propagation based on one study. Here, the annotation status of this protein family was examined through a comprehensive literature review and integrative bioinformatic analyses that revealed varied pleiotropic associations and phenotypes. This analysis combined with fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 199 publications
(257 reference statements)
1
19
0
Order By: Relevance
“…As a result, we first observed that disruption of the yqfO gene has a broad impact on genome gene expression. YqfO belongs to a large protein superfamily with unknown functions (DUF34), which is conserved in all three domains of life [ 11 ]. Although an exact mechanistic analysis was lacking, pleiotropic effects on physiological aspects, including transcription regulation, were observed in the disruptants of the genes encoding DUF34 proteins in many organisms [ 11 ].…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, we first observed that disruption of the yqfO gene has a broad impact on genome gene expression. YqfO belongs to a large protein superfamily with unknown functions (DUF34), which is conserved in all three domains of life [ 11 ]. Although an exact mechanistic analysis was lacking, pleiotropic effects on physiological aspects, including transcription regulation, were observed in the disruptants of the genes encoding DUF34 proteins in many organisms [ 11 ].…”
Section: Main Textmentioning
confidence: 99%
“…YqfO belongs to a large protein superfamily with unknown functions (DUF34), which is conserved in all three domains of life [ 11 ]. Although an exact mechanistic analysis was lacking, pleiotropic effects on physiological aspects, including transcription regulation, were observed in the disruptants of the genes encoding DUF34 proteins in many organisms [ 11 ]. The Thermus thermophilus DUF34 protein YbgI binds to single-stranded DNA [ 18 ], and the Geobacillus stearotherophilus DUF34 protein XynX regulates the xynA gene encoding xylanase through its binding to the xynA promoter [ 19 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…HcgD presumably works as an iron‐trafficking protein (Figure 10). [41] HcgD belongs to the Nif3 (NGG1p‐interacting factor 3)‐like protein family, a class of metalloproteins containing a dinuclear metal center [42] . As predicted, the crystal structure of HcgD from M. jannaschii presented a dinuclear iron‐binding site (Figure 10).…”
Section: Functional Analysis Of the Hcg Proteinsmentioning
confidence: 67%
“…If the HcgD functions as an iron‐trafficking protein, the toroid structure can dissociate with the functional dimer to interact with the partner enzyme responsible for the iron complex formation. A recent comparative genomic analysis of the Nif3 family proteins discusses about the metal ion‐insertion function [42] . However, other physiological functions of HcgD cannot be ruled out.…”
Section: Functional Analysis Of the Hcg Proteinsmentioning
confidence: 99%